2015
DOI: 10.1021/ma502322n
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Elastomers: Self-Assembling Star–Blocks of Soft Polyisobutylene and Hard Oligo(β-alanine) Segments

Abstract: A series of novel self-assembling star-blocks consisting of M w = 29 000 g/mol 3-arm polyisobutylene (PIB) stars and oligo(β-alanine) end segments were synthesized and characterized. Star−blocks containing β-alanine dimers are viscous liquids, while those with tri-, tetra-, and penta(β-alanine)s are elastic solids. According to IR spectroscopy, the β-alanine dimer is partially hydrogen-bonded, while the trimer, tetramer, and pentamer are fully hydrogen-bonded and form β-sheets. DSC suggests crystalline β-alani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 74 publications
1
24
0
Order By: Relevance
“…Jia et al [27] have recently evaluated thickness distribution of the hard segment domains for supramolecular elastomers (starblocks of soft polyisobutylene and hard oligo(β − alanine) segments). The molecule is a novel type of supramolecule as schematically shown in Figure 15 where the green chains are soft polyisobutylene.…”
Section: X-ray Scattering 124mentioning
confidence: 99%
See 1 more Smart Citation
“…Jia et al [27] have recently evaluated thickness distribution of the hard segment domains for supramolecular elastomers (starblocks of soft polyisobutylene and hard oligo(β − alanine) segments). The molecule is a novel type of supramolecule as schematically shown in Figure 15 where the green chains are soft polyisobutylene.…”
Section: X-ray Scattering 124mentioning
confidence: 99%
“…Black dots are for the experimentally obtained SAXS profile, and red curve is the calculated SAXS profile. The inset shows the evaluated thickness distribution [27].…”
Section: Spherical Casementioning
confidence: 99%
“…[12][13][14][15][16][17] In particular, rare-earth catalyst systems gave high cis content and high incorporation ratio of polar monomers simultaneously. [19] And it is also reported that oligo-alanine formed b-sheet [20] is part of hard segment of silk, which is mechanically strong and thermally stable. Considering potential large-scale manufacturing in the future,arare-earth catalytic system Nd(VA) 3 /Al(i-Bu) 3 /Al(i-Bu) 2 Cl was adopted in this work (Supporting Information, Scheme S2), which has already been successfully utilized in the industrial field.…”
mentioning
confidence: 99%
“…[19] And it is also reported that oligo-alanine formed b-sheet [20] is part of hard segment of silk, which is mechanically strong and thermally stable. [19] And it is also reported that oligo-alanine formed b-sheet [20] is part of hard segment of silk, which is mechanically strong and thermally stable.…”
mentioning
confidence: 99%
See 1 more Smart Citation